(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Chronic diseases are serious health concern all over the world and these are adding immense sufferings to millions of people. These remain persistent in one’s life and have long lasting effects on human life. Plant-based therapies can act as potential remedies to manage or cure these diseases with fewer, if not, no adverse effects and at a reasonable cost than the commercially available modern drugs. Furthermore, the constituents can be genetically modified to make them therapeutically effective against chronic diseases like diabetes, chronic inflammatory skin disease, chronic kidney disease, hypertension, cancer, ischemic heart disease and so on. Bombax ceiba Linn. is a tall, deciduous, multipurpose, miraculous tree that has numerous phytochemical constituents such as quercetin, carotenoids, β-sitosterol, α-tocopherol etc. along with shamimin, a novel compound that can help to treat chronic disorders. It has a long history for its medicinal uses. It is even highly regarded among aboriginal peoples for the remedy of various human and animal illnesses. Bangladesh Pharmaceutical Journal 26(2): 219-229, 2023 (July)